Electronic Effects versus Distortion Energies During Strain‐Promoted Alkyne‐Azide Cycloadditions: A Theoretical Tool to Predict Reaction Kinetics. Issue 18 (5th May 2013) - Garcia‐Hartjes, Jaime; Dommerholt, Jan; Wennekes, Tom; van Delft, Floris L.; Zuilhof, Han
Abstract: Second‐order reaction kinetics of known strain‐promoted azide–alkyne cycloaddition (SPAAC) reactions were compared with theoretical data from a range of ab initio methods. This produced both detailed insights into the factors determining the reaction rates and two straightforward theoretical tools that can be used to predict a priori the reaction kinetics of novel cyclooctynes for strain‐promoted cycloaddition reactions. Multiple structural and electronic effects contribute to the reactivity of various cyclooctynes. It is therefore hard to relate a physical or electronic property directly and independently to the reactivity of the cyclooctyne. However, we show that Hartree–Fock LUMO energies, which were acquired while calculating activation energies at the MP2 level of theory, correlate with second‐order kinetic rate data and are therefore usable for reactivity predictions of cyclooctynes towards azides. Using this correlation, we developed a simple theoretical tool that can be used to predict the reaction kinetics of (novel) cyclooctynes for SPAAC reactions. Abstract : Activation energies, distortion energies, and TS conformational data were compared in a set of strained cyclooctynes in strain‐promoted azide–alkyne cycloaddition (SPAAC) reactions. Only electronic effects could be accurately related to experimental rate data.